2011
DOI: 10.1111/j.1365-2524.2011.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

‘We are doing our best’: African and African-Caribbean fatherhood, health and preventive primary care services, in England

Abstract: Recent policy pronouncements emphasise the importance of engaging fathers with preventive primary care services. However, in England, there is a paucity of literature which examines African and African-Caribbean fathers' experiences of service provision. This paper reports a study that investigated African and African-Caribbean fathers' beliefs about fatherhood, health and preventive primary care services, with the aim of addressing the deficit in the literature. Nine focus groups involving 46 African and Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“…They were willing to approach and use health services but were unsure if this was appropriate or if the health professionals they consulted would have the relevant skills and knowledge base to deal with fathers’ mental health. That new fathers feel excluded by health professionals and unable to access appropriate information has been previously reported 24 30–35. Questioning the knowledge-base of family doctors and health visitors in relation to fathers’ mental health reported in this study was highlighted by Rowe et al , in an Australian study of 22 women and 16 men, where fathers suspected that the primary care health professionals were ‘not qualified to emotionally help you’ because their training prepared them to treat physical not mental illnesses (Rowe et al, p50, 51)[36].…”
Section: Discussionmentioning
confidence: 78%
“…They were willing to approach and use health services but were unsure if this was appropriate or if the health professionals they consulted would have the relevant skills and knowledge base to deal with fathers’ mental health. That new fathers feel excluded by health professionals and unable to access appropriate information has been previously reported 24 30–35. Questioning the knowledge-base of family doctors and health visitors in relation to fathers’ mental health reported in this study was highlighted by Rowe et al , in an Australian study of 22 women and 16 men, where fathers suspected that the primary care health professionals were ‘not qualified to emotionally help you’ because their training prepared them to treat physical not mental illnesses (Rowe et al, p50, 51)[36].…”
Section: Discussionmentioning
confidence: 78%
“…34-36 Research into the role of health visitors (public health nurses in the UK) found that they do not involve fathers in routine contacts 37 and were perceived by some fathers as a service provided “by women, for women”. 38 A Department of Health for England funded literature review on service users’ views suggested that some fathers welcomed the opportunity to express their feelings and emotions about fatherhood when asked by a healthcare professional, 39 but did not always have the opportunity to do this spontaneously. 40…”
Section: Introductionmentioning
confidence: 99%
“…Although the Pillars of the Ideal Healthy Community are a new framework, the individual pillars have all been identified as important to improving community health in prior research (Beydoun & Wang, 2008;Carver et al, 2008;Connell et al, 2007;Haskell et al, 2007;Perry et al, 1988). The core category, Hope for a Healthy Future, also aligned with existing research on health perceptions among minorities (Maton & Wells, 1995;Williams, Hewison, Stewart, Liles, & Wildman, 2012).…”
Section: Chapter V Discussionmentioning
confidence: 99%
“…In a qualitative study on the health perceptions of African fathers living in England, researchers asked participants about their perceptions related to fatherhood, health, and healthcare (Williams et al, 2012). The researchers found that participants were optimistic about the health of their children, and they were trying their hardest to be good fathers and to instill healthy habits in their children.…”
Section: Chapter V Discussionmentioning
confidence: 99%